Surface modification of carbon fuels for direct carbon fuel cells - Li, X.; Zhu, Z.; Chen, J.; De Marco, Roland; Dicks, A. (Elsevier, 2009)
The direct carbon fuel cell (DCFC) is a promising power-generation device that has much higher efficiency (80%) and less emissions than conventional coal-fired power plants. Two commercial carbons (activated carbon and carbon black) pre-treated with HNO3, HC1 or air plasma are tested in a DCFC. The correlation between the surface properties and electrochemical performance of the carbon fuels is explored. The HNO3-treated carbon fuels have the highest electrochemical reactivity in the DCFC due to the largest degree of surface oxygen functional groups. The overall effect on changing the electrochemical reactivity of carbon fuels is in the orderHNO3 > air plasma HC1. Product gas analysis indicates that complete oxidation of carbon to CO2 can be achieved at 600-700 C